Dakwah ibu bapa kepada anak-anak kajian dalam kalangan suku Banjar daerah Krian, Perak, Malaysia - Ismail Abdul Munir, Jemali Misnan, Daud Mohd Noor (N/A, 2014)
Dakwah ibu bapa kepada anak-anak kajian dalam kalangan suku Banjar daerah Krian, Perak, Malaysia by Ismail Abdul Munir, Jemali Misnan, Daud Mohd Noor,